TEKNOLOGI PENGEMASAN UNTUK MENINGKATKAN PEMASARAN PRODUK LOKAL MADU KELULUD DUSUN LIMBUNG BANGKA - Nyayu Siti Khodijah; Fournita Agustina; Mayarani Ginting (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Real work learning (KKN) is an academic obligation that must provide benefits for learning for students and provide solutions to problems in society in the form of smart creative ideas that are appropriate for the times. The socialization program for the right packaging technology to increase the marketing of superior products from Limbung, Jada Bahrin Village via online to creative business actors as part of the XV KKN_UBB Program with the theme "Creative Learning and Serving in the Covid 19 Period". The activity was attended by 15 students and 1 assistant lecturer. The implementation starts from June 22 to August 9 2020 in Limbung hamlet, Jada Bahrin village, Merawang district, Bangka regency. Activities include, observation activities to better understand social conditions, formulating activity items and real implementation in the form of products. Mentoring activities begin with mentoring in making product packaging designs by means of tutorials and practice, mentoring and teaching online marketing tutorials. The activity succeeded in designing, packaging kelulud honey products and assisting technology-based marketing using online media. The whole stages and program of activities show that after this KKN activity is felt to be beneficial for the community, and the community hopes for the sustainability of the program. Technological improvements in the form of training and mentoring in the management of product innovation, packaging appearance and online marketing strategies are still needed.